Implementation of Web-Based Administrative Payment Information System Using Laravel 10 Framework - Tatik Wulandari; Iwan Setiawan Wibisono (P3M Politeknik Negeri Bengkalis, 2025)
The development of information technology drives the need for an efficient data processing system, especially in the education sector. Madrasah Tsanawiyah NU 14 Kaligading manages financial administration manually, which causes various obstacles such as data inaccuracy and slow processes. This study aims to develop a web-based information system using the Laravel 10 framework to manage tuition payments in a more structured manner. The waterfall software development method encompasses needs analysis, system design, coding, testing, and maintenance. This system is designed to facilitate the management of school financial data with main features including user data input, payments, and student arrears. The implementation results show that the system can improve the efficiency and accuracy of financial management, accelerate the administration process, and facilitate real-time data access. In addition, this system also supports long-term data archiving, improves the effectiveness of administrative staff, and minimises errors in recording. This implementation is expected to help schools utilize modern technology to improve the quality of management and administrative services.